2019
DOI: 10.3390/biom9020066
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of SQUAMOSA—Promoter-Binding Protein (SBP) Genes Involved in the Flowering Development of Citrus Clementina

Abstract: SQUAMOSA-promoter binding protein (SBP)-box genes encode a family of plant-specific transcription factors that play vital roles in plant growth and development. In this study, 15 SBP-box genes were identified and isolated from Citrus clementina (CclSBPs), where 10 of these genes were predicted to be putative targets of Citrus clementina microRNA156 (CclmiR156). The 15 CclSBP genes could be classified into six groups based on phylogenetic analysis, diverse intron–exon structure, and motif prediction, similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 62 publications
5
28
0
Order By: Relevance
“…The results showed that CpSPL1 and CpSPL14 in G1 exhibited similar expression patterns, and the expression patterns of paralogous CpSPL9 and CpSPL15 in G5 showed high similarity. Our results were consistent with previous conclusion that paralogous SPL genes in the same group often showed similar expression pro les [46,47]. AtSPL9, AtSPL10, and AtSPL15 contribute to the vegetative to reproductive phase transition [8].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that CpSPL1 and CpSPL14 in G1 exhibited similar expression patterns, and the expression patterns of paralogous CpSPL9 and CpSPL15 in G5 showed high similarity. Our results were consistent with previous conclusion that paralogous SPL genes in the same group often showed similar expression pro les [46,47]. AtSPL9, AtSPL10, and AtSPL15 contribute to the vegetative to reproductive phase transition [8].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that CpSPL1 and CpSPL14 in G8 exhibited similar expression patterns, and the expression patterns of paralogous CpSPL9 and CpSPL15 in G6 showed high similarity. Our results were consistent with previous conclusion that paralogous SPL genes in the same group often showed similar expression profiles [45,46]. AtSPL9, AtSPL10 and AtSPL15 contribute to the vegetative to reproductive phase transition [8].…”
Section: Cpspl Genes' Expression Patterns In C Pilosulasupporting
confidence: 93%
“…(2005) Nishikawa et al. (2007) 14 CclSBP7 Clementine mandarin Arabidopsis thaliana Zeng et al. (2019) 15 miR3954 Citrus Hong Kong kumquat ( Fortunella hindsii ) Liu et al.…”
Section: Key Genes Associated With Citrus Domestication and Their Impmentioning
confidence: 99%
“…A total of 16 and 15 SBP-box genes have been identified in Arabidopsis and citrus, respectively. To understand the function of these genes, clementine mandarin SBP-box genes were cloned and overexpressed in Arabidopsis , and transgenic Arabidopsis plants expressing the CclSBP7 gene showed flowered earlier than control plants ( Zeng et al., 2019 ). These results indicate that CclSBP7 from is involved in early flowering in clementine mandarin and can induce early flowering in other citrus species to shorten the juvenile phase.…”
Section: Key Genes Associated With Citrus Domestication and Their Impmentioning
confidence: 99%